Cadherin expression and emt: A focus on gliomas - Noronha, C (2021)
Cadherins are calcium-binding proteins with a pivotal role in cell adhesion and tissue homeostasis. The cadherin-dependent mechanisms of cell adhesion and migration are exploited by cancer cells, contributing to tumor invasiveness and dissemination. In particular, cadherin switch is a hallmark of epithelial to mesenchymal transition, a complex development process vastly described in the progression of most epithelial cancers. This is characterized by drastic changes in cell polarity, adhesion, and motility, which lead from an E-cadherin positive differentiated epithelial state into a dedifferentiated mesenchymal-like state, prone to metastization and defined by N-cadherin expression. Although vastly explored in epithelial cancers, how these mechanisms contribute to the pathogenesis of other non-epithelial tumor types is poorly understood. Herein, the current knowledge on cadherin expression in normal development in parallel to tumor pathogenesis is reviewed, focusing on epithelial to mesenchymal transition. Emphasis is taken in the unascertained cadherin expression in CNS tumors, particularly in gliomas, where the potential contribution of an epithelial-to-mesenchymal-like process to glioma genesis and how this may be associated with changes in cadherin expression is discussed.